DINAMIKA PERAN SERIKAT PEKERJA NASIONAL DALAM MENGATASI PERSELISIHAN KONFLIK KOMUNIKASI ANTAR PEKERJA: STUDI KASUS ORGANISASI PSP. SPN PT. PARKLAND WORLD INDONESIA - Ferdiana, Riska; Mahmuda, Mahmuda; Gama, Aat Fatisti; Maliki, Budi Ilham (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Disputes between workers and representatives of the Workers’ Union are always a serious issue for the National Workers’ Union, where conflicts arise due to misunderstandings between the workers and the representatives of the National Workers’ Union. The purpose of this study is to understand the role of the National Workers’ Union in addressing and handling the dynamics occurring at PT. Parkland World Indonesia among the workers. The research method used by the author in this study is a descriptive qualitative method with a case study of internal organizational conflict and conflict management. The results and discussion on Conflict Management involve using interpersonal communication approaches and implementing strategies to avoid conflicts within the organization. Efforts and initiatives are key to reflecting and rejuvenating the organization through effective and efficient organizational communication with members, administrators, and the structural organization of the National Workers’ Union in Serang District, coordinated and effectively maintained with the Leadership of the Workers’ Union (PSP) SPN in each company.